Development of an Online Zakat Application System - Syed Othman, Syed Muhammad Arif; Yasak, Zurina (Research and Innovation in Technical and Vocational Education and Training, 2022)
File management better known as classical file management was handled by humans. There are too difficult to manage the file for an organization with only using manpower. However, with this sophisticated technology, such things can be best solved when using computer or file management systems. As a step towards capitalizing on the use of the technology system, this study was conducted to develop the Online Zakat Application System to assist students and the UTHM Islamic Center in particular in the application and management of zakat applicants’ data in UTHM. In addition, the system is also able to store application data in a computerized database in line with the era of computer technology use. In this study, the Waterfall development model was used to develop this system. For the evaluation process of the developed system, the expert checklist form and the expert confirmation form were distributed to the lecturer of the Faculty of Technical and Vocational Education as well as officials from the Islamic Center. The data obtained were analyzed using frequency and feedback analysis methods. The results of the study showed that all the experts have given a very positive response to the overall development of the system. As a result, this Online Zakat Application System has achieved the objectives of the study and received very positive feedback from the experts involved in the system evaluation process.